Analisis Biaya Dalam Perancangan Ulang Alat Pemotong Kripik Singkong Dalam Meningkatkan Kapasitas Dan Efisiensi Studi Kasus : UMKM Kripik Cassava - Afrilian, Krisna Surya Esa; Purnama, Jaka (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
This study aims to design a cassava chip-cutting machine to increase production capacity and efficiency at the MSME in Bumi Ayu Village, Malang City. Manual cutting results in long working hours and uneven slices. The research methodology includes surveys, problem identification, tool design, testing, and cost and productivity analysis. The findings show that the new tool can speed up cutting, increase production capacity, and meet consumer demand. Before the new tool, cutting productivity was 1.248 kg per hour, with a total of 3.125 kg per day. After implementing the new tool, cutting capacity is expected to increase by 50%, cutting time reduced by 40%, and total production output increased from 170 kg to 255 kg per week. The cost analysis shows a reduction in operational costs and a faster return on investment. This study proves that the new cutting tool can improve efficiency, reduce costs, and enhance the competitiveness of MSMEs in the market. Keywords: Cost Analysis, Cassava Chips, Productivity Analysis, Tool Design